STUDY OF CHARACTERIZATION AND BENEFICIATION OF IRON SAND FROM SOUTH BEACH OF WEST JAVA USING MULTISTAGE MAGNETIC SEPARATION - KALVIN T SITUMEANG (NIM : 12511023), ARMAND
The increasing number of Indonesian population also contributes to the increase of consumption of goods both by society and government. One of these goods is steel consumption. The development of the industrial sector and massive infrastructure development make the need for steel increase. However, the increase demand for steel is not followed by the increase of steel production. Iron sand is one of the raw materials for steel production. The development of iron sand processing is needed as a solution to increase steel production, mainly covering the beneficiary method/process. This research is aimed to study the characteristics and analysis of magnetic separation of iron sand using magnetic separators. The magnetic separation of iron sand originating from the south coast of West Java was studied by performing magnetic separation at various variations of magnetic force and multistages magnetic separation process. Experiments were carried out to investigate the characteristics of the iron sand beneficiation processes. Characteristics of the iron sand samples were determined by analysing the samples using X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), size by size analysis, and mineragraphic observation. Initial stage of experiments were carried out by performing magnetic separation on the samples using Davis Tube for pulverized samples and with variations in magnetic forces. Multistage magnetic separation processes were perfomed using Low Intensity Magnetic Separator (LIMS), Induced Roll Magnetic (IRM), and Davis Tube. Mineragraphy observations were also performed on the multistage magnetic separation products. The experimental results included sample characteristics (XRF, XRD, mineral grade of each size fraction, and initial sample mineragraphy observations) and characteristics of the magnetic separation products at various magnetic separation processes, i.e. %-weight and grade of the products. The results of sample characterization showed that magnetic minerals were still trapped in the impurities and their particle sizes were relatively fines. The experiments of magnetic separation using magnetic force of 1000 Gauss gave the optimum amount of magnetic product, and iron content and recovery, respectively. In multistage magnetic separation experiments using the LIMS and Davis Tube series resulted magnetic products with Fe grade and recovery of 55.39% and 41.06%, respectively, whilst experiments using the LIMS, Davis Tube, and IRM series gave magnetic products with Fe grade and recovery of 24.95% and 98.98%, respectively